Higher soluble TREM-1 levels are associated with cognitive impairment after acute ischemic stroke - Chen, Zhuo; Yi, Xin; Fu, Wei; Wu, Yong; Zhong, Xingju; Fan, Chaoli; Jiang, Yu; Zhou, Qi; Peng, Jie; Liao, Jieyu; You, Zhike; Tan, Jingyu (Frontiers in Aging Neuroscience, 2024)
Background and purposeTriggering receptor expressed on myeloid cells-1 (TREM-1) was reported to be critical for mediating the neurological function after stroke, while the impact of soluble TREM-1 (sTREM-1) on cognitive impairment after ischemic stroke is unclear. We aimed to explore the association between sTREM-1 and post-stroke cognitive impairment (PSCI).MethodsWe prospectively recruited consecutive ischemic stroke patients who admitted hospital within 7 days of onset. Serum sTREM-1 concentrations were measured after admission. Cognitive function was assessed at 90 days follow-up using the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA). PSCI was defined as a MMSE score of <27 or a MoCA score < 26.ResultsA total of 291 patients (mean age, 66.6 years; 46.0% female) were enrolled for this study. Among these participants, the median sTREM-1 concentrations were 289.4 pg/mL. According to the MoCA score, 153 (52.6%) patients experienced PSCI at 3 months. After adjustment for confounding risk factors by multivariate regression analysis, patients with sTREM-1 levels in the fourth quartile were more likely to have increased risk 3-month PSCI (as compared with the first quartile, odds ratio 12.22, 95% confidence intervals, 5.20–28.71, P = 0.001). Restricted cubic spline further confirmed a dose-dependent relationship between sTREM-1 levels and PSCI (P = 0.003 for linearity). Similar significant findings were observed when the cognitive impairment was diagnosed according to the MMSE criterion.ConclusionOur study revealed that higher serum sTREM-1 levels at admission were associated with increased risk of 3-month PSCI.